The Chemistry of the Degenerative Disease - Marco Brito-Arias (The Chemistry of the Degenerative Disease, 2025)
The book describes a group of pathologies catalogued as the most representative degenerative disease affecting the skeletal, motor and neural systems, considered a global health problem with high impact, producing disability, decay in the quality of life, decline of memory and cognitive capacities as well as depressive associated behaviour. Significant progress has been made to ameliorate the progression of these illnesses as shown in this book covering different strategies including small drug therapies, the use of synthetic oligonucleotides, humanised antibodies, recombinant proteins and gene-modified approach, with highly promising results, although unfortunately not yet sufficient to revert and restore the full capacities. The book also describes the principles of neurotransmission, neurotransmitters, receptor agonists and antagonists, allosteric modulators, and opioid receptors with the aim of providing additional support to understand neuronal functioning and how they are gradually impaired during a degenerative disease progression. Finally, the book explains the cellular mechanisms involved during the degenerative disease advance, including signalling pathways, inflammation processes, immune response, oxidative stress-associated factors and genetic alterations.